MENELADANI KEPEMIMPINAN RASULULLAH SAW : MENJADI PEMIMPIN YANG RESPONSIBLE - Nur Aisah Rahmah; Ahmadi Ahmadi (JURNAL ILMIAH NUSANTARA, 2025)
This article discusses the concept of responsible leadership by emulating the leadership of the Prophet Muhammad as the central figure in Islamic teachings. Leadership in Islam does not only focus on the end result, but also emphasizes ethical responsibility, social justice, and exemplary morals. This research applies the literature study method by analyzing various sources of literature, hadith, and theories regarding modern and Islamic leadership. The findings show that the Prophet implemented the principles of leadership based on trustworthiness, justice, empathy, and ethics in all aspects of life as a leader in spiritual, social, and political matters. His concern for the community, firmness in upholding justice, and forgiving and modest attitude are important examples for today's leadership challenges. This article states that the Prophet's leadership model can be used as a strong basis in shaping leaders who not only have skills, but also have integrity and are able to bring good changes in the midst of a moral and social crisis.